Influence of a Salinity Gradient on the Vessel Characters of the Mangrove Species Rhizophora mucronata - SCHMITZ, NELE (Oxford University Press, 2006)
• Background and Aims Although mangroves have been extensively studied, little is known about their ecological wood anatomy. This investigation examined the potential use of vessel density as a proxy for soil water salinity in the mangrove species Rhizophora mucronata (Rhizophoraceae) from Kenya. • Methods In a time-standardized approach, 50 wood discs from trees growing in six salinity categories were investigated. Vessel densities, and tangential and radial diameters of rainy and dry season wood of one distinct year, at three positions on the stem discs, were measured. A repeated-measures ANOVA with the prevailing salinity was performed. • Key Results Vessel density showed a significant increase with salinity, supporting its use as a prospective measure of salinity. Interestingly, the negative salinity response of the radial diameter of vessels was less striking, and tangential diameter was constant under the varying environmental conditions. An effect of age or growth rate or the presence of vessel dimorphism could be excluded as the cause of the absence of any ecological trend. • Conclusions The clear trend in vessel density with salinity, together with the absence of a growth rate and age effect, validates the potential of vessel density as an environmental proxy. However, it can only be used as a relative measure of salinity given that other environmental variables such as inundation frequency have an additional influence on vessel density. With view to a reliable, absolute proxy, future research should focus on finding wood anatomical features correlated exclusively with soil water salinity or inundation frequency. The plasticity in vessel density with differing salinity suggests a role in the establishment of a safe water transport system. To confirm this hypothesis, the role of inter-vessel pits, their relationship to the rather constant vessel diameter and the underlying physiology and cell biology needs to be examined.